Integrating Total Quality Management And Management Control Systems - Restina Purba; Meylin Amanda Simalango; Iman Suyakin Daeli; Jufri Darma (ACCOUNT: Jurnal Akuntansi, Keuangan dan Perbankan, 2025)
In the face of global competition, organizations need to integrate Total Quality Management (TQM) with Management Control Systems (MCS) to manage performance more effectively. While TQM emphasizes quality, customer satisfaction, and continuous improvement, MCS provides formal and informal mechanisms to ensure the achievement of strategic objectives. This study aims to examine the relationship, contribution, and challenges of integrating TQM and MCS through a Systematic Literature Review (SLR) of articles published between 2021 and 2025, using content analysis and narrative synthesis. The findings indicate that their synergy strengthens strategic alignment, quality culture, and control systems, thereby enhancing organizational effectiveness, with key success factors including leadership, quality-oriented culture, incentives, and technological support. Overall, the integration of TQM and MCS creates a balance between cultural flexibility and the rigor of control systems, making it highly relevant for both business and public sectors.